Harry Potter and the goblet of fire - Rowling, J. K. (Rowling, J. K. Harry Potter series, 2000)
When the Quidditch World Cup is disrupted by Voldemort's rampaging supporters and the terrifying Dark Mark is resurrected, it is obvious to Harry that Voldemort is getting stronger. The ultimate symbol to the magic world of the evil Lord's return would be if the one and only survivor of his death curse, Harry Potter, could finally be beaten.